2022
DOI: 10.3390/ijerph19159427
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Physical-Activity-Based Interventions Targeting Overweight and Obesity among University Students—A Systematic Review

Abstract: Overweight and obesity, including their prevalence and consequences, reflect a leading public health problem. Studies have already shown that physical activity leads to a reduction in body weight in children and adults. However, the university setting has rarely been investigated. The aim of this review is, therefore, to examine and summarize the effectiveness of physical-activity-based interventions to reduce obesity and overweight in university students. Three databases (PubMed, Scopus, and Web of Science) w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…Albeit physical-activity-based interventions varying substantially between their intervention approaches, most of them have been demonstrated to have a positive impact on young people [26,51,52]. While not all of the studies showed significant effects on decrementing BMI, nevertheless, all of the studies reported at least one significant improvement in indicator-related health, such as improvements in body fat percentage, sedentary behavior, or serum biomarkers [51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albeit physical-activity-based interventions varying substantially between their intervention approaches, most of them have been demonstrated to have a positive impact on young people [26,51,52]. While not all of the studies showed significant effects on decrementing BMI, nevertheless, all of the studies reported at least one significant improvement in indicator-related health, such as improvements in body fat percentage, sedentary behavior, or serum biomarkers [51].…”
Section: Discussionmentioning
confidence: 99%
“…Albeit physical-activity-based interventions varying substantially between their intervention approaches, most of them have been demonstrated to have a positive impact on young people [26,51,52]. While not all of the studies showed significant effects on decrementing BMI, nevertheless, all of the studies reported at least one significant improvement in indicator-related health, such as improvements in body fat percentage, sedentary behavior, or serum biomarkers [51]. It is noteworthy to mention that there are also studies that did not report significant enhancements in obesity, BMI, and the WHR, and subsequently the various interventions [52,53], and that in some studies, an adequate control group was missing [54].…”
Section: Discussionmentioning
confidence: 99%
“…Exercise interventions involve systematically structured physical activity programmes specifically tailored for the purpose of elevating fitness levels, supporting weight management endeavours, and augmenting overall health parameters (Boukrim et al, 2021). These programmes, specifically designed to cater to the unique requirements of obese college students, may encompass aerobic activities, strength training regimens, or a synergistic combination of both modalities (Pfisterer et al, 2022). Conversely, nutrition interventions are pivotal in effecting positive modifications in the dietary behaviours of the targeted student cohort.…”
Section: Nutritional and Exercise Interventionmentioning
confidence: 99%
“…However, limited research specifically addresses the impact of exercise and dietary interventions on body image among obese college students (Grajek et al, 2022), a population facing unique challenges, including social stigma and media portrayal, which significantly influence body image perceptions (Koulanova et al, 2021). Consequently, there is a critical need to investigate the impact of these interventions on obese college students, gaining insights into their efficacy and tailoring interventions accordingly (Pfisterer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Students face new challenges throughout this shift, including deciding for themselves what to study and how to live, adjusting to the demands of an unstructured classroom, and engaging with a wide variety of new people (Hernández-Torrano et al, 2020). In recent years, there have been multiple studies targeting university students for research (Ho & Lim, 2021;Pfisterer et al, 2022).…”
Section: Introductionmentioning
confidence: 99%